Territorial Identities in the Electoral Preferences Formation Process (an Example of the Election in Lugansk) - Khobta, Svitlana (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article is devoted to the role of territorial identities in the process of formation of the electoral preferences on the example of the elections in the city of Lugansk (2008-2012). It is shown that the electoral preferences are influenced by the identities, but the effect is not decisive. This is only one of many factors. In the dynamics of territorial identities there was noticed a rise of urban identity and decline of the regional one, but according to the author’s opinion, it is not a manifestation of destruction of its potential. Elections to the Verkhovna Rada of Ukraine in 2012 continue regionalization of the political arena of the country, and political manipulations on the basis of regional differences have a quite high potential to be used in all-Ukrainian political process.